Extracellular Vesicles in Neuroinflammation - Marostica, Giulia; Gelibter, Stefano; Gironi, Maira; Nigro, Annamaria; Furlan, Roberto (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are a heterogeneous group of membrane-bound particles that play a pivotal role in cell-cell communication, not only participating in many physiological processes, but also contributing to the pathogenesis of several diseases. The term EVs defines many and different vesicles based on their biogenesis and release pathway, including exosomes, microvesicles (MVs) and apoptotic bodies. However, their classification, protocols of their isolation and detection and their biological functions are still under investigation. Recent evidence suggests the existence of novel subpopulations of EVs, increasing the degree of heterogeneity between EV types and subtypes. EVs have been shown to have roles in the CNS as biomarkers and vehicles of drugs and other therapeutic molecules. They are known to cross the blood-brain barrier, allowing CNS EVs to be detectable in peripheral fluids and their cargo could give information about the origin cells and the pathological process they are involved in. In this review, we summarized the function of the EVs in the pathogenesis of multiple sclerosis (MS) and discuss recent evidence for their potential applications as diagnostic biomarkers and therapeutic targets.